Outcome and prognostic factors of postoperative radiation therapy (PORT) after incomplete resection of non-small cell lung cancer (NSCLC) - Hörner-Rieber, Juliane; Deeg, Kai Alexander; Bulut, Elena; Förster, Robert; Bischof, Marc; Warth, Arne; Schnabel, Philipp A.; Muley, Thomas; Kappes, Jutta; Heußel, Claus Peter; Welzel, Thomas; Thomas, Michael; et al. (Lung cancer, 2016)
Purpose - Current guidelines recommend postoperative radiation therapy (PORT) for incompletely resected non-small cell lung cancer (NSCLC). However, there is still a paucity of evidence for this approach. Hence, we analyzed survival in 78 patients following radiotherapy for incompletely resected NSCLC (R1) and investigated prognostic factors. - Patients and methods - All 78 patients with incompletely resected NSCLC (R1) received PORT between December 2001 and September 2014. The median total dose for PORT was 60Gy (range 44-68Gy). The majority of patients had locally advanced tumor stages (stage IIA (2.6%), stage IIB (19.2%), stage IIIA (57.7%) and stage IIIB (20.5%)). 21 patients (25%) received postoperative chemotherapy. - Results - Median follow-up after radiotherapy was 17.7 months. Three-year overall (OS), progression-free (PFS), local (LPFS) and distant progression-free survival (DPFS) rates were 34.1, 29.1, 44.9 and 51.9%, respectively. OS was significantly prolonged at lower nodal status (pN0/1) and following dose-escalated PORT with total radiation doses >54Gy (p=0.012, p=0.013). Furthermore, radiation doses >54Gy significantly improved PFS, LPFS and DPFS (p=0.005; p=0.050, p=0.022). Interestingly, survival was neither significantly influenced by R1 localization nor by extent (localized vs. diffuse). Multivariate analyses revealed lower nodal status and radiation doses >54.0Gy as the only independent prognostic factors for OS (p=0.021, p=0.036). - Conclusion - For incompletely resected NSCLC, PORT is used for improving local tumor control. Local progression is still the major pattern of failure. Radiation doses >54Gy seem to support improved local control and were associated with better OS in this retrospective study.
Gesehen am 18.06.2020